# `3x^2-x=56` solve for x

*print*Print*list*Cite

### 3 Answers

Given the equation:

`3x^2 - x = 56`

==> `3x^2 -x -56= 0`

We have a quadratic equation which we can use by factoring or using the quadratic formula.

==> `x= (-b+-sqrt(b^2-4ac))/(2a)`

==> `x1= (1+sqrt(1+4*3*56))/(2*3)`

==> `x1= (1+sqrt(672))/6 = (1+4sqrt42)/6`

==> `x2= (1-4sqrt42)/6`

Then, we have two roots.

`==> x' = { (1+4sqrt42)/6 , (1-4sqrt42)/6 }`

### User Comments

3x^2-x=56

3x^2-x-56=0

Use the quadratic formula to get: -4.14 and 4.4 as your roots.

3x^2-x=56

3x^2-x-56=0

now you must use the quadratic formulae and get: -4.14 / 4.4 as your roots.^_^